Electro-Optic Co-Simulation in High-Speed Silicon Photonics Transceiver Design Using Standard Electronic Circuit Simulator - Keisuke Kawahara; Toshihiko Baba (IEEE Journal of Microwaves)
The increasing demand for high-speed optical interconnects requires the integration of photonics and electronics, with electro-optic (EO) co-simulation being crucial. However, fragmented electronic/photonic simulators and incomplete models, which do not include the radio-frequency characteristics and noise, are still prevalent, and thus, an EO co-simulation environment for high-speed transceiver design has not yet been established. Here, we present a unified and experimentally validated EO co-simulation library that enables accurate transmission performance predictions at symbol rates exceeding 50 Gbaud. Specifically, we model passive photonic components, such as waveguides and couplers, as well as two types of Si Mach–Zehnder modulators, incorporating frequency-dependent lossy traveling-wave electrodes and slow-light enhancement. We also show models for test equipment with validated noise characteristics, including an erbium-doped fiber amplifier (EDFA), a tunable filter, and a photodetector module, to construct a full optical link testbench. The S-parameter simulations agreed well with measurements up to 40 GHz, and the signal transmission simulations matched measurements up to 64 Gbps. All models and sample testbenches are available on GitHub.